An investigation of key competitiveness indicators and drivers of full-service airlines using Delphi and AHP techniques - Delbari, Seyyed Ali; Ng, Siew Imm; Abdul Aziz, Yuhanis; Ho, Jo Ann (Elsevier, 2016)
The purpose of this study was to identify and prioritize the key competitiveness indicators and drivers of full-service airlines. To achieve this, the study used a two-phase, sequential exploratory mixed methods research that was initiated with a qualitative phase (Delphi technique), and followed by a quantitative phase (Analytic Hierarchy Process technique). The results of the qualitative phase revealed that full-service airlines need to pay attention to the 12 key indicators and 15 key drivers to evaluate and improve their competitiveness status, respectively. The key identified indicators include quality, safety, price, connectivity, timeliness, flight frequency, profitability, productivity, cost, market share, customer loyalty, and revenue growth, and the key identified drivers are including bargaining power of customers, bargaining power of suppliers, rivalry among existing competitors, government policies, physical resources, financial resources, human resources, technological resources, reputational resources, flight operations capabilities, engineering and maintenance capabilities, marketing and services capabilities, finance and property capabilities, personnel capabilities, and strategic alliances. Further, the results of the quantitative phase demonstrated that profitability is the most important key competitiveness indicator, closely followed by productivity. It was also found that generally bargaining power of customers is the most powerful key competitiveness driver, and followed by financial resources. However, the results revealed that the ranking of the key competitiveness drivers with respect to each indicator differs significantly. The findings of this research provide important implications for the evaluation and improvement of the competitiveness status of full-service airlines.